Contested Puberty: Judicial Discretion, Moral Regulation, and the Persistence of Child Marriage in Indonesia - Y Sonafist; Azhar; Syukrawati; Nurjanah Nurjanah; Wail Abouabaid (PT. Islamic Research Publiser, 2026)
The 2019 revision of Indonesia's Marriage Law raised the minimum marriage age to 19, yet produced a striking paradox: rather than reducing child marriage, it precipitated a sharp increase in marriage dispensation applications in religious courts. This article argues that the reform displaced the site of legitimation for child marriage—shifting authorization from administrative registration to judicial approval through dispensation mechanisms—revealing not merely a failure of legal implementation, but a deeper process through which the state and judiciary actively reproduce the legal boundaries of adulthood and child protection. Drawing on a socio-legal framework, this study employs critical discourse analysis of two complementary sites: the normative constructions embedded in the Marriage Law—particularly the ambiguous phrase